Thermo-flexible resin for the 3D printing of occlusal splints: A randomized pilot trial - Herpel, Christopher; Kykal, Jana; Rues, Stefan; Schwindling, Franz Sebastian; Rammelsberg, Peter; Eberhard, Lydia (Journal of dentistry, 2023)
Objectives - To compare the clinical performance of occlusal splints printed from thermo-flexible resin with milled splints. - Methods - A parallel two-arm pilot trial was initiated. Forty-seven patients (n women=38) were recruited from a tertiary care center and randomized using an online tool (sealed envelope). Inclusion criterion was an indication for treatment with a centric relation occlusal splint due to bruxism or any form of painful temporomandibular disorder. Patients were excluded if they were younger than 18 years, unable to attend follow-up appointments, or required another type of splint therapy. Patients received either, a 3D-printed (intervention group, V-print splint comfort, VOCO) or a milled splint (control group, ProArt CAD splint, Ivoclar). Construction software Ceramill M-splint (AmannGirrbach), 3D-printer MAX UV 385 (Asiga) and milling unit PrograMill PM7 (Ivoclar) were used. Follow-up assessments were conducted after 2 weeks and 3 months. Outcome measures were survival, adherence, technical complications, patient satisfaction on a 10-point Likert scale, and maximum wear using superimposition of optical scans. - Results - After 3 months, 20/23 intervention group and 18/24 control group participants were assessed. All splints survived. Minor complications were small crack formations on 6 printed and 4 milled splints. Mean patient satisfaction was 8 (SD 1.7) for printed, and 8.1 (SD 2.3) for milled splints (r = 0.1, p = .52). Median maximum wear was highly dispersed with 153 (IQR 140) in posterior and 195 (IQR 537) in frontal segments of printed, and 96 (IQR 78) respectively, 123 (IQR 155) of milled splints, (both: r = 0.31, p = .084). - Conclusions - Within the limitations of a pilot trial, 3D-printed and milled splints performed similarly in terms of patient satisfaction, complication rates and wear behavior. - Clinical significance - Thermo-flexible material was proposed for 3D printing of occlusal splints to overcome mechanical weaknesses of previously available resins. This randomized pilot study provides evidence that this material is a viable alternative to milled splints for at least three months of clinical use. Further evidence on long-term use should be obtained.
Online verfügbar 7. April 2023, Artikelversion 14. April 2023
Gesehen am 19.06.2023